THE EFFECTIVENESS OF USING CHARADES GAME FOR ENGLISH VOCABULARY MASTERY TO STUDENTS AT SDN 18 PALEMBANG - Msy. Rabi'atul Adawiyah; Jaya Nur Iman (Dirasah: Jurnal Pemikiran dan Pendidikan Dasar Islam, 2025)
Nowadays, the majority of students lack mastery of vocabulary. Besides, students are also lack interested in studying English which ultimately made their English performance decreased or even poor. Game is an alternative to increase students’ vocabulary, one of them is using charades game. Therefore, the objectives of this research were to find out whether there was the effectiveness of using charades game in improving English vocabulary mastery students and to know students’ perceptions towards charades game in studying English vocabulary. This research was utilized quantitative research and pre-experimental group design. The sample was all of students in the 6th grade which were 20 students of SDN 18 Palembang. To gather the data, pre-test, post-test, and questionnaire were administered. After obtaining and analyzing the data, it was found that the mean score of pre-test was 47.75, while the post-test was 78.5. It meant that the mean score of post-test was higher than the pre-test. It could be pointed out that the use of charades game could improve students’ vocabulary mastery. Students also showed positive perceptions of charades game. Students agreed that charades game increased their motivation, made them happy, relax, enjoy, and more enthusiastic, also helped them easier in studying vocabulary.